ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA KOPERASI KONVENSIONAL DAN KOPERASI SYARIAH - Gusniati Puteri; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine and analyze the soundness of the liquidity ratios, solvency, and profitability of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City during the 2014-2018 period. And to find out the fulfillment of the financial performance standards of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City, based on liquidity ratios, solvency ratios and profitability ratios during the period 2014-2018.This study uses secondary data in the form of data obtained by the author through, manual reports and financial reports of the Umega Prima Trade and Services Cooperative and the Al-Ittihad BMT Cooperative in Pekanbaru City that are needed by researchers for the analysis of liquidity, solvency, and profitability.The results of the analysis show that the analysis of the financial statements of the Trade Cooperative and Prima Umega Services for the period 2014 - 2018 based on Liquidity, Solvency and Profitability Ratios are: 1) Analysis of liquidity ratios, qurrent ratios get the predicate "Not Good", and the cash ratio gets the predicate "Not good" "; 2) Solvency ratio analysis, the total asset to debt ratio gets the title "good", and the net worth to debt ratio gets the "good" title; 3) Analysis of the ratio of profitability of one's own capital gets the title "not good", and return on assets gets the title "not good"; 4) In accordance with the regulations of the State Ministry for Cooperatives, Small and Medium Enterprises, the health level of umega trade and prime services cooperatives is rated "unhealthy". While the results of the analysis of the 2014-2018 BMT Al-Ittihad Cooperative based on Liquidity, Solvency and Profitability Ratios are: 1) Analysis of liquidity ratios, qurrent ratios get the predicate "Poor", and in the cash ratio get the predicate "good"; 2) Solvency ratio analysis, the total asset to debt ratio gets the predicate "less good", and the net worth to debt ratio gets the predicate "good"; 3) Analysis of the ratio of profitability of one's own capital gets the title "very good", and return on assets gets the title of "very good"; 4) In accordance with the regulations of the State Ministry for Cooperatives, Small and Medium Enterprises, the health level of the cooperative bmt al-ittihad kota Pekanbaru gets the title "quite healthy". Keywords: Comparison of Financial Performance, Liquidity, Solvency and profitability